Ground Settlements due to Construction of Triplet Tunnels with Different Construction Arrangements - Ahsan Naseem; Ken Schotte; Bart De Pauw; Hans De Backer (Advances in Civil Engineering)
Combining two or three shield tunnels that are drilled consecutively at small intermediate distances into a single open cross section creates a larger useful tunnel area, while keeping the total construction area rather compact. However, the combination of several bored tunnel tubes into a singular cross section results in a complicated construction procedure. Current methodologies address the evaluation of the settlement trough for one single tunnel or two parallel tunnels only. This study aims at expanding the current methodologies to the multiple-tunnel geometry. Various construction orders and intermediate distances between the tunnels are evaluated using finite element analyses. The grout pressure method is applied in combination with the hardening strain with the small strain stiffness (HS small) constitutive model to investigate the relative magnitude of the settlements due to shield tunneling. It is concluded that the configuration with a Top-Left-Right construction sequence is the optimal arrangement. It results in 22.4% and 36.9% lesser settlements when compared to the equivalent horizontal twin tunnels spaced at 3D and the Left-Right-Top sequence, respectively.